SNR enhancement in OTDR using pulse coding - Xie, Yi. (2009)
The traditional Optical Time Domain Reflectometer (OTDR), which uses single optical pulse, extends the dynamic range by increasing the pulse width. However, the increment of pulse width will result in the decrease of the spatial resolution. So the high spatial resolution and long dynamic range can’t be obtained simultaneously. To optimize the two parameters at the same time, one applicable approach is to employ pulse coding and trace decoding technique for probe lights and reflect signals, respectively. Gray Codes and Biorthogonal sequence were proposed to be used in the OTDR, with a better performance than the traditional single-pulse one. however, as the optical fiber communication systems are getting longer and longer, above achievements are not enough to meet the higher and higher requirement to the dynamic range.